The Role of ARL4C in Erlotinib Resistance: Activation of the Jak2/Stat 5/β-Catenin Signaling Pathway - Liao, Jinrong; Chen, Zeng; Yu, Zongyang; Huang, Tao; Hu, Dan; Su, Ying; He, Zhiyong; Zou, Changyan; Zhang, Lurong; Lin, Xiandong (Frontiers in Oncology, 2020)
Cancer patients who initially benefit from Erlotinib，a drug targeting EGFR path, eventually develop resistance to the drug. The underlying mechanism is largely unknown. This study investigated the role of ARL4C in mediating Erlotinib resistance in NSCLC. The qRT-PCR and Western blotting were performed to analyze the expression of mRNA and protein of ARL4C (ADP-ribosylation factor-like 4C) in two NSCLC cell lines (HCC827 and PC-9). Several assays (MTS, colony formation, transwell migration, luciferase reporter and chroma-tin-immunoprecipitation) were used to explore the role of ARL4C in the biofunctions of Erlotinib resistant cells and their associations with Jak2/Stat 5/β-catenin signalings. Results demonstrated that: (1) the long-term use of Erlotinib resulted in down-regulation of ARL4C; (2) the overexpression of ARL4C could regain the sensitivity to Erlotinib in the resistant HCC827/ER cells, while downregulation of ARL4C increased Erlotinib resistance of HCC827 and PC-9 cells; (3) Erlotinib-induced down-regulation of ARL4C resulted in phosphorylation of Jak2/Stat5 and up-regulation of β-catenin and their related Axin2, CD44, Ccnd1, Lgr-5 and MMP7, which promoted the malignant behaviors of Erlotinib-resistant cells; (4) the results of chromatin-immunoprecipitation and luciferase reporter assay revealed that Stat5 could bind to β-catenin promoter to upregulate molecules to maintain the malignant behaviors, which might count for how Erlotinib resistant cell survived while EGFR path was blocked ; (5) the expression of ARL4C was not associated with known EGFR gene mutations both in Erlotinib resistant cells and NSCLC tissues. Our data suggest that Erlotinib resistance of NSCLCs is associated with downregula-tion of ARL4C via affecting Jak/Stat/β-catenin signaling. ARL4C could serve as a biomarker to predict the effectiveness of TKI-based targeted therapy and a potential therapeutic target for over-coming Erlotinib resistance in NSCLC.